Ethnic and sex differences in ambulance activation among hospitalized patients with acute coronary syndromes: Insights from the Alberta contemporary acute coronary syndrome patients invasive treatment strategies (COAPT) study. (1st December 2018) - Bainey, Kevin R.; Alemayehu, Wendimagegn; Gupta, Arjun K.; Bowker, Samantha L.; Welsh, Robert C.; Kaul, Padma
Abstract: Background: With acute coronary syndromes (ACS), activation of emergency medical services (EMS) ensures early treatment. However, EMS activation remains under-utilized. We examined whether ground EMS use varied by sex or ethnicity among a population-based cohort of ACS patients. Methods: We used linked administrative health datasets to identify patients who were hospitalized with an ACS (April 1, 2002-March 31, 2016). Validated naming algorithms were used to categorize patients according to ethnicity (Caucasian, South Asian, Chinese). Results: Of the 60, 717 patients with an ACS (male: 41, 175; female: 19, 542), 42.3% presented to hospital via ground ambulance. Compared to males, females were more likely to activate EMS (38.9% vs. 49.3%, p  < 0.001). Compared to the Caucasians ( n  = 58, 666), EMS activation was significantly higher among Chinese ( n  = 793) (42.1% vs. 49.8%; p  = 0.0007) and slightly higher in South Asians ( n  = 1258) (42.1% vs. 44.7%; p  = 0.45). The relatively higher EMS use among females was maintained across the ethnic groups. In multivariable adjusted analyses, females were more likely to use EMS compared to males (OR: 1.31; 95% CI: 1.26–1.36). Compared to the Caucasians, a weaker trend towards South Asian and Chinese EMS activation was observed (OR: 1.08; 95% CI 0.96–1.21; OR: 1.10; 95% CI 0.95–1.28, respectively). In the male cohort only, South Asians and Chinese tended to activate EMS more often than the Caucasians (Males: South Asian OR: 1.14; 95% CI 1.00–1.31, Chinese OR: 1.15; 95% CI 0.96–1.38; Females: South Asian OR: 0.93; 95% CI 0.75–1.15, Chinese OR: 1.01; 95% CI 0.77–1.30). Conclusion: EMS use was sub-optimal and differed based on sex and ethnicity. Our results reinforce the need for targeted public health efforts to enhance ambulance activation. Highlights: In a population-level cohort study of ACS patients we found: Only a 42.3% EMS activation rate for ACS. Female sex was independently associated with EMS activation. A trend towards ethnic differences in EMS activation for ACS among Chinese and South Asian migrants.